2001
DOI: 10.1103/physreve.64.041909
|View full text |Cite
|
Sign up to set email alerts
|

Turing model for the patterns of lady beetles

Abstract: We simulate the patterns on the hard wings of lady beetles using a reaction-diffusion equation based on the Turing model. A part of a spherical surface is used to approximate the geometry of the hard wings. Various patterns common to lady beetles in Taiwan can be produced on this curved surface by adjusting the parameters of the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Varea et al (1999) have considered pattern formation on spherical surfaces while Chaplain et al (2001) investigate patterns on the radially growing sphere. Liaw et al (2001) show that the patterns exhibited by a Turing reaction-diffusion system on a fixed portion of a sphere resemble closely those observed on lady beetles (ladybirds). Moreover, their preliminary study suggests that curvature does not alter significantly the results for the case of planar domains.…”
Section: Discussionsupporting
confidence: 52%
“…Varea et al (1999) have considered pattern formation on spherical surfaces while Chaplain et al (2001) investigate patterns on the radially growing sphere. Liaw et al (2001) show that the patterns exhibited by a Turing reaction-diffusion system on a fixed portion of a sphere resemble closely those observed on lady beetles (ladybirds). Moreover, their preliminary study suggests that curvature does not alter significantly the results for the case of planar domains.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast to the case of a fixed domain, numerous different stripe and spot patterns occur depending on perturbations of the initial conditions for the model. Further examples of studies of RDEs illustrating the role of domain growth can be found in papers by Varea et al (1999), Chaplain et al (2001), Liaw et al (2001), Painter et al (1999), Crampin et al ( , 1999, Oster and Bressloff (2006), Madzvamuse et al (2003Madzvamuse et al ( , 2005, Madzvamuse (2005) and for a review see Plaza et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Turing patterns on a growing sphere were recently investigated numerically by Chaplain et al [8] in an application to metastasis in a growing tumor. Liaw et al [17] simulated a Turing model on part of a spherical surface and showed that they could reproduce various patterns that are exhibited on the hard wings of lady beetles.…”
Section: Introductionmentioning
confidence: 99%